A Hybrid Grid‐Based Finite‐Element Approach For 3D Steel Casing Forward Modeling. Issue 2 (18th November 2021) - Yu, Nian; Gao, Lei; Li, Ruiheng; Wu, Xialan; Wang, Enci
Abstract: Steel casing forward modeling often requires considering the slender casing in the study area to study the influence of this casing on the underground electromagnetic field, which can be implemented by the unstructured finite‐element (FE) method based on tetrahedra. However, the calculation efficiency of applying the unstructured FE method directly to the steel casing model is poor. To this end, this article develops an FE approach based on a hybrid grid by using slender prismatic elements to mesh the steel casing area, while the remaining areas are still discretely meshed with tetrahedra. By showing numerical examples of the vertical single steel casing and L‐shaped steel casing models, the advantages of the method are tested by evaluating the response curves and the degrees of freedom. The results show that prismatic elements are suitable for discretizing steel casing areas. This approach can maintain the high accuracy of the numerical solution and reduce the number of elements required for discretizing the steel casing area. Hybrid grids can greatly increase the computational efficiency of the FE method for steel casing forward modeling. Abstract : The calculation result of the hybrid mesh of the steel casing L2 approaches that of tetrahedral mesh. The enlarged view shows that the electric field Ex curve of the hybrid mesh has smaller fluctuations than the tetrahedral mesh. This shows that the hybrid mesh can obtain smooth and stable calculation results while reducing the number of degrees of freedom.